2022
DOI: 10.14245/ns.2244956.478
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Strategies and Perioperative Considerations for Cervical Deformity With Cerebral Palsy: A Comprehensive Review of the Literature

Abstract: The complex nature of the cervical spine makes surgical intervention challenging when treating cervical deformity in patients with cerebral palsy (CDCP). However, few studies have investigated the unique characteristics of cerebral palsy that create the need for surgery, the most effective surgical strategies, and the possible perioperative complications. The intended benefit and the potential risk of postoperative complications must be considered when deciding to operate for CDCP. Because the approach and cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 67 publications
0
3
0
Order By: Relevance
“…Harada et al reported an eight-fold increase in cervical disc degeneration and midcervical instability, predisposing to stenosis and neurologic deterioration [28]. Cervical myelopathy occurs in the 40 s, earlier than the general population [29,30]. Poor head control, increased muscle tone, and abnormal gait predispose to cervical degeneration [29].…”
Section: Spinementioning
confidence: 99%
See 2 more Smart Citations
“…Harada et al reported an eight-fold increase in cervical disc degeneration and midcervical instability, predisposing to stenosis and neurologic deterioration [28]. Cervical myelopathy occurs in the 40 s, earlier than the general population [29,30]. Poor head control, increased muscle tone, and abnormal gait predispose to cervical degeneration [29].…”
Section: Spinementioning
confidence: 99%
“…Cervical myelopathy occurs in the 40 s, earlier than the general population [29,30]. Poor head control, increased muscle tone, and abnormal gait predispose to cervical degeneration [29]. Athetoid CP, in particular, is a predisposing risk factor to cervical instability, myelopathy, and functional deterioration [9,29,31].…”
Section: Spinementioning
confidence: 99%
See 1 more Smart Citation